Prophetic Conflict in Ancient Israel and its Reflections in the Christian Community in Nigeria - Awojobi, Peter Olanrewaju; Adesina, Ifejesupo Gbolafunmi (NIU Journal of Humanities, 2024)
This study argued that the activities of the prophetic groups in ancient Israel brought prophetic ministry into disrepute. As a corollary, the study explored the parallel between prophetic groups in ancient Israel and different Christian groups and denominations in Nigeria. The study was premised on Historical and African Biblical Hermeneutics. It was discovered that there existed parallel between prophetic groups in ancient Israel and the Christian Community in Nigeria. Study revealed that despite the Prophets’ and the Church leaders’ claims to have been divinely called and commissioned the duo were defending and protecting their group, identity, doctrines and interest at the detriment of their divine call as the mouthpiece of God. This action brought the ministries in both contexts into disrepute and decline, for their audience no longer take their oracles and ministries seriously. Their audience see them more of representatives of their prophetic group or church affiliation than of God. The study concludes that church leaders and members of the Christian community in Nigeria should intentionally build a good interpersonal and interdenominational relationship that will cut across group and denominational boundaries in order to foster unity and peaceful coexistence among Christians and non-Christians in Nigeria. Keywords: Prophetic Conflict, Ancient Israel, Christian Community, Church leaders and Nigeria.